Suami Schizophrenia Menjaga Isteri Bipolar Mood Disorder?: Satu Kajian Kes - Hanieza Fadzlina Yahya; Tuti Iryani Mohd Daud; Mohd Izwan Mahmud (Universiti Sains Islam Malaysia, 2024)
E-Proceeding Marital and Sexuality Counseling Seminar (MASEC 2021) “Keluarga Sejahtera: Cabaran di Abad 21” “Family Well-Being: Challenges in the 21st Century” 22 September 2021 Organized by: Counseling Programme, Faculty of Leadership and Management, USIM In collaboration with:Sa’adah Counseling and Consultation Centre for Wellbeing (Sa’adah Centre)